Effect of Roasting Time and Temperature on Volatile Component Profiles during Nib Roasting of Cocoa Beans (Theobroma cacao) - Jinap, S.; Wan Rosli, W. I.; Russly, A. R.; Nordin, L. M. (Wiley, 1998)
The e†ect of nib roasting time and temperature on volatile component proÐles was studied using response surface methodology (RSM) which consisted two independent variables : time (5È65 min) and temperature (110È170¡C). A steam distillation extraction (SDE) method was used to extract and gas chromatographÈmass spectrometry equipped with an ICIS data system was used to identify the volatile compounds. Tetramethylpyrazine, trimethylpyrazine, phenethyl acetate, isoamyl acetate, 3-methylbutyl acetate, phenylacetaldehyde, benzaldehyde and 2-phenylethanol were present in all treatments. Pyrazine formation increased as roasting time and temperature were increased. The number of pyrazines increased from 4 to 11 and 25, respectively, when roasting, time was increased from 5 to 35 and 65 min at 140¡C. The unit area of esters increased (up to 1700È1800) when the roasting time was increased from 15 to 65 min (at 110È 120¡C). However, the unit area of carbonyls linearly decreased with an increasing roasting temperature at shorter time (5È25 min). The unit area of phenols was enormously reduced at the highest roasting temperature (160È170¡C) with longest roasting time (45È65 min) while that of alcohol slightly decreased as roasting time and temperature were increased